Impact of COVID-19 on mild vascular cognitive impairment in patients with atrial fibrillation: results of a three-year observational study - O. V. Vorob'eva; N. N. Shindryaeva; V. V. Fateeva (Неврология, нейропсихиатрия, психосоматика)
The relationship between vascular cognitive impairment (VCI) and atrial fibrillation (AF) is mediated by multiple mechanisms, including vascular risk factors associated with a more severe course of COVID-19.Objective: to investigate the impact of COVID-19 on the dynamics of cognitive status parameters in patients with AF over an observation period of 36 months.Material and methods. The observational study included 51 patients (19 men and 32 women; age ranged from 46 to 73 years, mean age 57.7 years) who met the inclusion criteria. All study participants were tested at baseline and after 36 months using Montreal Cognitive Assessment (MoCA). The study took place during COVID-19 pandemic, and 25.5% of patients had documented SARS-CoV-2-associated pneumonia. During the observation period, patients received stable background therapy to prevent modifiable vascular risk factors. Two groups were formed: group 1 (n=13) — COVID-19 “+”, group 2 (n=38) — COVID-19 “-”. Patients in group 1 were more likely to have stage IIIarterialhyper-tension (46.2% vs. 17.9% in group 2; p<0.05), had a history of ischemic stroke (38.5% vs. 5.3% in group 2; p<0.05), were not vaccinated with Gam-COVID-Vac vaccine (23.1% vs. 73.7% in group 2; p<0.05).Results. Patients with AF after SARS-CoV-2 virus infection experienced deterioration of VCI from 22.7±2.1 to 20.2±1.6 points according to MoCA (p<0.05) due to impairments in executive functions, attention, memory and speech. After 36 months of observation, the number of patients with a memory index score <7 points, which indicates a high risk of conversion of mild cognitive impairment to dementia, increased by 30.7% in group 1 and by 5.3% in group 2 (p<0.05).Conclusion. Patients with atrial fibrillation who had COVID-19 showed a more pronounced progression of cognitive impairment despite the constant use of stable background therapy aimed at correcting modifiable vascular risk factors.